Hydrolysis of Protein and Model Dipeptide Substrates by Attached and Nonattached Marine Pseudomonas sp. Strain NCIMB 2021 - Griffith, Peter C. (1991)
Rates of substrate hydrolysis by nonattached bacteria and by bacteria attached to particles derived from marine diatom frustules were estimated by using two substrates, a dipeptide analog and a protein. Adsorption of the two substrates onto the particles was also evaluated. Methyl-coumarinyl-amide-leucine (MCA-leucine) was used to estimate hydrolysis of dipeptides by measuring an increase in fluorescence as MCA-leucine was hydrolyzed to leucine and the fluorochrome methylcoumarin. To examine hydrolysis of a larger molecule, we prepared a radiolabeled protein by (14)C-methylation of bovine serum albumin. The rate of protein hydrolysis in samples of particle-attached or nonattached bacteria was estimated by precipitating all nonhydrolyzed protein with cold trichloroacetic acid and then determining the trichloroacetic acid-soluble radiolabeled material, which represented methyl-(14)C-peptides and -amino acids. About 25% of the MCA-leucine adsorbed to the particles. MCA-leucine was hydrolyzed faster by nonattached than attached bacteria, which was probably related to its tendency to remain dissolved in the liquid phase. In contrast, almost 100% of the labeled protein adsorbed to the particles. Accordingly, protein was much less available to nonattached bacteria but was rapidly hydrolyzed by attached bacteria.